Additive-modulated PEDOT:PSS for efficient perovskite-based light-emitting diodes - Suriani Abdul Latiff (Nanyang Technological University, 2022)
Poly (3,4 ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) has been extensively used in perovskite-based light-emitting diodes (PeLEDs) due to its high transmittance, temperature stability, and favorable energy band alignment with commercially available transparent conducting electrodes such as indium tin oxide (ITO) makes it a good candidate for the hole transport layer. However, its limitations lie within its low hole conductivity and additives engineering can be used to solve this problem. Three types of additives to modulate the conductivity and work function of PEDOT:PSS were studied: perfluorinated polymer (Nafion), Poly (sodium 4-styrenesulfonate) (PSS-Na), and poly(ethylene) glycol (PEG). The effect on the conductivity, work function, surface energy, and HTL/perovskite interfaces quality to eventually linking them to PeLED performances of their respective devices were elaborated. Various concentrations of each dopant were scrutinized and compared. In increasing order of the best performing devices from each additive, (PEDOT:PSS):Nafion of ratio 10:1 exhibited 1.93% External Quantum Efficiency (EQE%), followed by (PEDOT:PSS):PSSNa at 2.36% and the champion device from PEG-modified PEDOT:PSS at a remarkable EQE of 2.7%.